A facile liquid/liquid interface method to synthesize graphyne analogs. Issue 46 (21st May 2019) - Song, Yuwei; Li, Xiaodong; Yang, Ze; Wang, Jing; Liu, Chunyue; Xie, Chipeng; Wang, Huanlei; Huang, Changshui
Abstract : A novel interfacial synthetic approach for preparing varieties of gauze-like graphyne analogs. Abstract : An innovative facile interfacial synthetic strategy is demonstrated as a general method for the synthesis of graphyne analogs (GYs), which are composed of benzene rings connected by acetylenic bonds. All these synthesized GYs, which are obtained as uniform films in microscopic morphology, exhibit outstanding conductive properties, endowing excellent applications in many electrical devices.